Sagittanthera (Hyacinthaceae, Urgineoideae), a new buzz pollinated genus from the Eastern Cape Province of South Africa - Martínez-Azorín, Mario; Crespo, Manuel B.; Dold, Anthony P.; Wetschnig, Wolfgang; Pinter, Michael; Pfosser, Martin; van Jaarsveld, Ernst (Phytotaxa, 2013)
Within the framework of a taxonomic revision of subfamily Urgineoideae, we here describe a new genus from south-eastern South Africa. Sagittanthera gen. nov. is at first sight related to Rhadamanthus and Tenicroa, but it can be clearly differentiated by the presence of bracteoles and the anthers connate to form a cone-like structure dehiscing by minute apical pores. This genus is based on Rhadamanthus cyanelloides, an enigmatic species occurring in the Eastern Cape Province of South Africa. It was described on the basis of incomplete material. Recently, Drimia cremnophila and D. mzimvubuensis, two species that match the diagnostic characters of the new genus, were described from the same region. A complete description is presented for Sagittanthera, and data on morphology, ecology, and distribution are also reported. Two species are accepted in this genus, and the necessary combinations are stated. Furthermore, we demonstrate that pollen is released by vibration. This fact together with morphological features of the androecium clearly evidence that buzz pollination occurs in this new genus.